2016
DOI: 10.1002/smi.2724
|View full text |Cite
|
Sign up to set email alerts
|

Emotional contagion and burnout among nurses and doctors: Do joy and anger from different sources of stakeholders matter?

Abstract: The present study adds novel knowledge to the literature on emotional contagion (EC), discrete emotions, job burnout, and the management of healthcare professionals by simultaneously considering EC as both a job demand and a job resource with multiple social pathways. Integrating EC into the job demands-resource model, we develop and test a conceptual model wherein multiple stakeholder sources of emotional exchanges (i.e., leaders, colleagues, patients) play a differential role in predicting caregivers' absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 53 publications
(56 reference statements)
0
66
0
1
Order By: Relevance
“…According to the literature, the most frequently mentioned risk factors of occupational burnout include personality traits, attitude to work and burden related to the doctor's satisfaction, organization and working conditions [1,2]. Attempts to observe the connections between socio-demographic and psychosocial determinants of burnout in contemporary doctors have frequently become the subject of research [3,4,5,6,7]. Occupational burnout is usually presented from the perspective of the theoretical model developed by Cristine Maslach (Maslach Burnout Inventory-MBI), describing three dimensions of professional burnout among medical staff: emotional exhaustion, depersonalization and a sense of lack of personal achievement [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the most frequently mentioned risk factors of occupational burnout include personality traits, attitude to work and burden related to the doctor's satisfaction, organization and working conditions [1,2]. Attempts to observe the connections between socio-demographic and psychosocial determinants of burnout in contemporary doctors have frequently become the subject of research [3,4,5,6,7]. Occupational burnout is usually presented from the perspective of the theoretical model developed by Cristine Maslach (Maslach Burnout Inventory-MBI), describing three dimensions of professional burnout among medical staff: emotional exhaustion, depersonalization and a sense of lack of personal achievement [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has documented that emotional contagion is a predictor of burnout. For example, consistent with the Job Demands-Resource (JD-R) model of work-related stress [34], a study by Petitta, Jiang, and Härtel [35] found that contagion of anger absorbed from others may serve as a job demand that is related to increased job burnout, whereas contagion of joy may serve as a job resource that is related to reduced burnout. Indeed, contagion of a positive emotion (i.e., joy) may facilitate social bonding, cooperation, and synchronization of opportunities [36].…”
Section: Emotional Contagion Infected and Job Burnoutmentioning
confidence: 89%
“…Taking the perspective of the employee as perpetrator or initiator, the present study examined a model of antecedents and consequences of instigated incivility. Building on the JD-R model of etiology of burnout incorporating the contagion of positive/negative emotions infected into others as job resources/demands [34,35], a stressor-emotion model [40], and the "broaden and build" model [45], we tested a crosscountry model of employee instigated incivility as a mediator linking the contagion of one's own positive (joy) and negative (anger) emotions infected into others and one's burnout.…”
Section: Discussionmentioning
confidence: 99%
“…General findings of prior research indicate that emotional exhaustion is a widespread phenomenon with severe outcomes for employees and organizations (Alarcon, 2011;Cropanzano, Rupp, & Byrne, 2003). While there is extensive research on the antecedents and consequences of employee emotional exhaustion, there is limited research on how a supervisor's emotional exhaustion influences employees (Bakker, Westman, & Hetty van Emmerik, 2009;Hobfoll, Halbesleben, Neveu, & Westman, 2018;Petitta, Jiang, & Härtel, 2017;Ten Brummelhuis, Haar, & Roche, 2014;Wirtz, Rigotti, Otto, & Loeb, 2017). Existing research focuses on crossover theory (Bakker, Westman, & Schaufeli, 2007;Westman, 2001) and suggests that supervisor emotional exhaustion influences employee emotional exhaustion through emotional contagion (Bakker et al, 2009), negative affect (Ten Brummelhuis et al, 2014), and increased job demands (Chullen, 2014).…”
Section: Sonuçmentioning
confidence: 99%
“…Stres alanyazınında bu kavramın diğer birçok kavram ile ilişkisi detaylı bir şekilde ortaya konmaktadır (Alarcon, 2011;Cropanzano, Rupp ve Byrne, 2003). Ancak duygusal tükenmişlik yaşayan bireylerin (örn., yönetici, çalışan) birbirlerini nasıl etkiledikleri de gittikçe önem kazanan bir araştırma alanıdır (Bakker, Westman ve Hetty van Emmerik, 2009;Hobfoll, Halbesleben, Neveu ve Westman, 2018;Petitta, Jiang ve Härtel, 2017;Ten Brummelhuis, Haar ve Roche, 2014;Wirtz, Rigotti, Otto ve Loeb, 2017). Özellikle günümüzde sürekli yükselen iş taleplerinin, iş ortamlarında tükenmişliği arttırıcı bir etkisi bulunmaktadır.…”
unclassified